Assessment of heavy metals in wild and farmed tilapia (Oreochromis niloticus) on Lake Kariba, Zambia: implications for human and fish health. Issue 1 (2nd January 2022) - Simukoko, Chalumba Kachusi; Mwakalapa, Eliezer Brown; Bwalya, Patricia; Muzandu, Kaampwe; Berg, Vidar; Mutoloki, Stephen; Polder, Anuschka; Lyche, Jan Ludvig
ABSTRACT: The aim of this study was to assess the levels of heavy metals in both wild and farmed tilapia on Lake Kariba in Zambia and to evaluate the impact of intensive fish farming on wild tilapia. Three sites for wild fish (2 distant and 1 proximal to fish farms) and two fish farms were selected. One hundred fish (52 from distant sites; 20 near fish farms; 28 farmed fish) were sampled and muscle tissues excised for analysis of heavy metals (Mg, Fe, Zn, Al, Cu, Se, Co, Mo, As, Cr, V, Ni, Hg, Pb, Li, Cd, and Ag) by acid (HNO3 ) digestion and ICP-MS. All metals were found to be below the maximum limits (MLs) set by WHO/EU. Essential metals were higher in farmed tilapia, whereas non-essential metals were higher in wild tilapia. Significantly higher levels of essential metals were found in wild fish near the fish farms than those distant from the farms. Estimated weekly intake (EWI) for all metals were less than the provisional tolerable weekly intakes (PTWI). Target hazard quotients (THQ) and Hazard Indices (HI) were <1, indicating no health risks from a lifetime of fish consumption. Selenium Health Benefit Value (HBVSe ) was positive for all locations, indicating protective effects of selenium against mercury in fish. Total cancer risk (CR) due to As, Cr, Cd, Ni and Pb was less than 1 × 10 −4, indicating less than 1 in 10, 000 carcinogenic risk from a lifetime consumption of tilapia from Lake Kariba. Hg levels (0.021 mg/kg) in wild tilapia at site 1 were higher than the Environmental quality standard (EQS = 0.020 mg/kg) set by EU, indicating possible risk of adverse effects to fish. Except for Hg, levels of metals in fish were safe for human consumption and had no adverse effects on fish. Graphical abstract: uf0001